A comparison of the calculated creatinine clearance level between gestational hypertension and chronic hypertension during pregnancy and postpartum - Kamaruddin, Mardhiah (2016)
Introduction: Hypertension is present in approximately up to 10% of all pregnancies worldwide., and also one of the leading causes of morbidity and mortality in pregnancy. Hypertensive disorders during pregnancy may cause the long-term complications and consequences after a decade having hypertension during pregnancy. Hypertensive disorders during pregnancy is also highly associated with end-stage renal disease. Objective: This study compared the reduction of creatinine clearance level between gestational and chronic hypertension patient from pregnancy to post-delivery. This study aimed to assess the level of mean difference of calculated creatinine clearance within group (gestational hypertension and chronic hypertension), the mean difference of calculated creatinine clearance between groups regardless of time and the mean difference of calculated creatinine clearance between groups based on time. Methods: A prospective cohort study was performed on patients with gestational and chronic hypertension at Hospital Universiti Sains Malaysia. The total of 10 pregnant mothers from each group were recruited during their third trimester of pregnancy from Obstetrics & Gynaecology Clinic of Hospital USM. The patients were consented and medical record was reviewed at recruitment (third tritnester). Patients had the blood taking of renal function test for every visit at third trimester, six weeks after delivery and 12 weeksafter delivery. The creatinine clearance was calculated by using Modification of Diet in Renal Disease formula. Repeated Measure AN COY A analysis was applied with birth weight and gestational age at delivery were controlled. Results: For within group analysis, there was a significant difference of mean calculated creatinine clearance within gestational hypertension and chronic hypertension based on time after controlling potential covariates (birthweight and gestational age at delivery) (F=21.59, p=0.002). Multiple comparisons was performed with adjusted a based on Bonferroni correction. The results showed that there were significant differences in pair 1 (third trimester-six weeks postpartum; mean difference: 25.99; 95%CI: 19.84, 32.14; p<0.001) and pair2 (third trimester-12 weeks postpartum: mean difference: 23.66; 95% CI: 9.63, 37.64; p=0.003) in gestational hypertension group. In the meantime, all comparison groups were significant in chronic hypertension participants. Multiple comparisons showed that there were significant differences in pair 1 (third trimester-six weeks postpartum; mean difference: 27 .02; 95% CI: 18.15, 35.90; p<O.OO 1 ), pair 2 (third trimester-12 weeks postpartum: mean difference: 28.85; 95% CI: 20.75, 36.96, p<0.001) and pair 3 (six weeks postpartum-12 weeks postpartum: mean difference: 1.83; 95% CI: 0.41, 3.25; p=0.015). Meanwhile, there was no significant difference of mean calculated creatinine clearance between gestational hypertension and chronic hypertension (F=l.59, p=0.266) regardless of time. For time-treatment interaction results in repeated measure ANOV A analysis, there was no significant difference of mean calculated creatinine clearance between groups based on time (F= 0.56, p= 0.579). But, we still proceed to multiple comparison to determine if there was a significant difference for each time. From the results, there was a significant difference of calculated creatinine clearance at 12 weeks postpartum (p=0.023). For other measurement, there was no significant difference of mean creatinine clearance between this two groups. When comparing the creatinine clearance from thirdtrimester to 12 weeks postpartum, chronic hypertension group showed a big reduction of calculated creatinine clearance with mean difference of 28.85 ml/min. Patient with gestational hypertension had increase in creatinine clearance at 12 weeks postpartum but the creatinine clearance level in chronic hypertension tend to decrease by 1.83 mllmin at 12 weeks postpartum. Conclusion: The regular check-up during postpartum especially on renal function is encouraged in \Vomen with a history of hypertensive disorders in pregnancy as it is one of the important issues to consider due to the chance of having renal disorder after several years of pregnancy.